Pesan-pesan Dakwah Toleransi Muhammadiyah pada Instagram @Lensamu - Anugerah, Feri (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2020)
The Muhammadiyah movement is oriented towards da'wah so that its main focus is to embrace as many people as possible. As a da'wah movement, Muhammadiyah always tries to embrace, including the concept of tolerance. The ultimate goal is to create the common good with the principle of inclusivity as a guideline. For Muhammadiyah, da'wah is a whole process to invite people to Islam which can be done through various aspects of community development activities. In this case, Muhammadiyah's activities in the fields of tablig, education, social, and economics are held for the interest and for the purpose of da'wah. This research aims to find out what and how the Muhammadiyah tolerance da'wah messages are like on social media @Lensamu. Based on the results of the research, the following findings were obtained. First, there is sociological diversity within the Islamic organization of Muhammadiyah which includes a group called Muhammadiyah Christianity which has been documented in a book based on field research by two authors. Second, Muhammadiyah shows the message of tolerance through active interaction with individuals or groups of different faiths, especially in the field of education. Third, Muhammadiyah's tolerance is also reflected in the testimonies of Catholic students about their experiences studying at Muhammadiyah's campus. Keywords: Muhammadiyah, da'wah, message, tolerance, Krismuha